Late Woodland Pottery Production in Essex County, Ontario: Evidence from the Puce Site - Williamson, Chiara (University of Waterloo, 2020)
This thesis examines a collection of Early Late Woodland (Western Basin Tradition) pottery from the Puce Site (AbHq-3) in St. Clair Shores, Essex County, Ontario. The site was discovered through a Cultural Resource Management Stage 2 property assessment, and subsequent archaeological work was undertaken to excavate the site. Using an attribute analysis, 51 earthenware vessels recovered during these excavations are examined using 11 different variables: Nature of Specimen, Castellation form, Upper Rim Profile, Rim Form, Lip Thickness, Collar Height, Surface Modification, Decorative Completeness, Tool, Technique, and Motif. This analysis indicates that the pottery producers at Puce were employing design methods associated with the late Riviere au Vase and early Younge phases of the Western Basin Tradition. Results show that cord wrapped instruments were the preferred tool of executing decorative motifs, while stamping techniques and discontinuous linear oblique lines were the most common design elements found within the collection. These traits are common during the Early Late Woodland in the lower Great Lakes region. Finally, these data are compared to the nearby Silverman site, and other sites in the region, in an effort to elucidate the presence of local design patterns in pottery production.
Keywords: Indigenous; stewardship; pottery; vessels; Western Basin Tradition; ceramics; quantitative attribute analysis; Woodland pottery; Woodland culture; Woodland Indians; Indian pottery; Ethnoarchaeology; Essex (Ont. : County)